2021
DOI: 10.3390/jcm10061313
|View full text |Cite
|
Sign up to set email alerts
|

Management of Dyspepsia and Gastroparesis in Patients with Diabetes. A Clinical Point of View in the Year 2021

Abstract: Diabetes mellitus is a widespread disease, and represents an important public health burden worldwide. Together with cardiovascular, renal and neurological complications, many patients with diabetes present with gastrointestinal symptoms, which configure the so-called diabetic enteropathy. In this review, we will focus on upper gastrointestinal symptoms in patients with diabetes, with particular attention to dyspepsia and diabetic gastroparesis (DG). These two clinical entities share similar pathogenetic mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 66 publications
2
7
0
Order By: Relevance
“…Diabetes mellitus is a widespread disease. According to the International Diabetes Federation, it affects 463 million people worldwide with an increasing prevalence [ 1 ]. Diabetes is an important public health burden, mainly because of its cardiovascular, renal, and neurological complications.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus is a widespread disease. According to the International Diabetes Federation, it affects 463 million people worldwide with an increasing prevalence [ 1 ]. Diabetes is an important public health burden, mainly because of its cardiovascular, renal, and neurological complications.…”
Section: Introductionmentioning
confidence: 99%
“…16 Moreover, patients with DMT1 may show higher levels of HP colonization because of delayed gastric emptying and the occurrence of gastroparesis, as the result of autonomic neuropathy. 17 Chung et al demonstrated that the incidence of microalbuminuria was significantly higher in patients with DMT2 and coexisting HPI. 18 Similarly, in a study by Zizzi et al, it was found that HPI is associated with a higher incidence of proteinuria in patients with DMT2.…”
Section: Discussionmentioning
confidence: 99%
“…AST [U/L]19(16)(17)(18)(19)(20)(21)(22)(23)(24) ALT [U/L] 19(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) Creatinine[μmol/L] 79.6 (70.7-88.4) eGFR [mL/min/1.73 m 2 ] 87.6 (76.5-90) hsCRP [mg/dL] 1.5 (0.8-3.1) T-Ch [mmol/L] 48 (41.6-53.8) TAG [mmol/L] 1.1 (0.83-1.5) HDL-C [mmol/L] 1.6 (1.3-2) LDL-C [mmol/L] 2.6 (2.1-3.1) non-HDL-C [mmol/L] 3.1 (2.6-3.6) 25-OH vitamin D [mg/dL] 19 (13-29) VAI-K, n 1.8 (1.4-2.9) VAI-M, n 2.5 (1.6-4.1) eGDR [mg/kg/min] 8.2 (6-9.4) AGEs, SAF 2.2 (1.9-2.7) AGEs -advanced glycation end products; ALT -alanine aminotransferase; AST -aspartate aminotransferase; BMI -body mass index; DBP -diastolic blood pressure; DDI -daily dose of insulin; eGFR -estimated glomerular filtration rate; eGDR -estimated glucose disposal rate; HbA1c -glycated hemoglobin A1c; HC -hip circumference; HDL-C -…”
mentioning
confidence: 99%
“…However, smokers with diabetes could not benefit from dual antiplatelet therapy after AIS or TIA. Some underlying mechanisms may contribute to the abnormal pharmacokinetics of clopidogrel in patients with diabetes, such as decreased gastrointestinal drug absorption, increased prodrug and AM hydrolysis [8,27]. Moreover, the decreased efficacy of antiplatelet therapy is also related to platelet hyperactivity and the inhibition of the P2Y 12 signaling pathway in patients with diabetes [28].…”
Section: Discussionmentioning
confidence: 99%